Five new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Borneo, with a key to the Bornean species and new faunistic data - Borowiec, Lech; Takizawa, Haruo; Świętojańska, Jolanta (Zootaxa, 2013)
Five new species of Notosacantha are described from Borneo (Sabah): N. flaviventris Borowiec and Takizawa sp. nov. (also described from Sumatra), N. flavosuturata Świętojańska and Takizawa sp. nov., N. minuta Świętojańska and Takizawa sp. nov., N. obscuricornis Borowiec and Takizawa sp. nov. and N. ovoidea Borowiec and Świętojańska sp. nov. New records for nine other species, a check list and key to Bornean Notosacantha are given. Myrsinaceae and Myristicaceae are new host plant families for tortoise beetles and Ardisia elliptica Thunb., Ardisia sp., Embelia sp., Gironiema sp. (all Myrsinaceae) and Knema sp. (Myristicaceae) are new host plants for Notosacantha.